Development of novel salicylic acid-donepezil-rivastigmine hybrids as multifunctional agents for the treatment of Alzheimer's disease - Yi Zhou; Ying He; Xue Teng; Jing Mi; Jing Yang; Rongrui Wei; Wenmin Liu; Qinge Ma; Zhenghuai Tan; Zhipei Sang (Taylor & Francis Group, 2023)
Alzheimer's disease (AD) is a chronic, progressive brain degenerative disease that is common in the elderly. So far, there is no effective treatment. The multi-target-directed ligands (MTDLs) strategy has been recognised as the most promising approach due to the complexity of the pathogenesis of AD. Herein, novel salicylic acid-donepezil-rivastigmine hybrids were designed and synthesised. The bioactivity results exhibited that 5a was a reversible and selective eqBChE inhibitor (IC50 = 0.53 μM), and the docking provided the possible mechanism. Compound 5a also displayed potential anti-inflammatory effects and significant neuroprotective effect. Moreover, 5a exhibited favourable stabilities in artificial gastrointestinal solution and plasma. Finally, 5a demonstrated potential cognitive improvement in scopolamine-induced cognitive dysfunction. Hence, 5a was a potential multifunctional lead compound against AD.